HBR guide to critical thinking - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2023)
"You're facing a problem at work. There are many ways you can approach the issue, but they each come with their own pros and cons. How do you sort through the information at hand so that you know you're taking the right path? The solution is in how you think. The HBR Guide to Critical Thinking will help you use reasoning and logic to navigate your most challenging issues, from complex problems to tough decisions to tricky situations. By carefully observing, gathering information, and analyzing what's in front of you, you can feel comfortable moving forward while building this crucial leadership skill. You'll learn how to: examine your assumptions; apply data where necessary; keep an open mind to opposing views; surface hidden biases; grow comfortable with ambiguity; and learn and grow"--
Improve Your Critical Thinking at Work : How to learn this essential skill / an interview with Helen Lee Bouygues by Curt Nickisch -- Beware the Urgency Trap : Allow yourself time to think / by Jesse Sostrin -- Act Like a Scientist : Be a knowledgeable skeptic / by Stefan Thomke and Gary W. Loveman -- To Change the Way You Think, Change the Way You See : De-familiarize yourself from what you know / by Adam Brandenburger -- Are You Solving the Right Problems? : Reframe them to reveal unexpected solutions / by Thomas Wedell-Wedellsborg -- Write a Better Problem Statement : Imprecise language can lead to poor solutions / by Daniel Markovitz -- Zoom In, Zoom Out : Understand when to focus and when to pull back / by Rosabeth Moss Kanter -- Critical Thinking Starts with Careful Questioning : Apply rigor to your curiosity / by John Coleman -- Four Types of Questions to Achieve Four Different Goals : Reach better conclusions and avoid tedious rework / by Tom Pohlmann and Neethi Mary Thomas -- Think Critically About Your Data : How was it sourced, how was it analyzed, and what was left out? / by Eric Haller and Greg Satell -- Stop Asking "Why" and Start Asking "How" : It will help you focus on the future / by Alan H. Palmer -- A New Way to Become More Open-Minded : Start by admitting you might be wrong / by Shane Snow -- Take a More Flexible Approach to Your Decision Making : Involve other people to break tired habits and avoid cognitive bias / by Cheryl Strauss Einhorn -- Disagreement Doesn't Have to Be Divisive : Engage and learn, even when your viewpoints clash / by Francesca Gino -- When Group Discussion Backfires : Discuss data; don't predict outcomes / by Joshua Becker, Douglas Guilbeault, and Edward "Ned" Smith -- Three Ways Leaders Can Listen with More Empathy : Techniques to help you hear, process, and respond / by Christine M. Riordan -- 3 Ways to Improve Your Decision Making : Start by being less c
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 10, 2023).
Added to collection customer.56279.3
Keywords: Critical thinking; Problem solving; Decision making; Industrial management; Success in business; Critical thinking; Decision making; Industrial management; Problem solving; Success in business; elektronické knihy; electronic books